2011
DOI: 10.1007/s00455-011-9383-8
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Tongue Activity During Swallowing in Mouth-breathing Children

Abstract: Habitual mouth breathing is often accompanied by habitual anterior tongue thrust, instead of a lip closure, in order to create the anterior seal necessary for the initiation of physiological deglutition. We tested the null hypothesis of no significant influence of oral maneuver and the use of oral screens on tongue coordination and position during deglutition in 29 subjects (age = 6–16; mean = 9.69 years; 13/16 female/male) with habitual open-mouth posture using intraoral polysensography. The target parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…Our findings of increased force and activity of the tongue-protruding muscles and a sustained contraction force, when accompanied by the lip incompetence in mouth breathing (9,20), suggest that, in mouth-breathing patients, changes in the tongue musculature may contribute to several malocclusions, thus altering the shape of the craniofacial complex. In cases of nasal obstruction, there could be not only increased activity of the tongue-protruding muscles, but also a possible increase in their force.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Our findings of increased force and activity of the tongue-protruding muscles and a sustained contraction force, when accompanied by the lip incompetence in mouth breathing (9,20), suggest that, in mouth-breathing patients, changes in the tongue musculature may contribute to several malocclusions, thus altering the shape of the craniofacial complex. In cases of nasal obstruction, there could be not only increased activity of the tongue-protruding muscles, but also a possible increase in their force.…”
Section: Discussionmentioning
confidence: 70%
“…The possible maintenance of a forward tongue position with an increased force is critical for the effectiveness of orthodontic and myofunctional therapy in mouth-breathing children (20). Our findings of increased force and activity of the tongue-protruding muscles and a sustained contraction force, when accompanied by the lip incompetence in mouth breathing (9,20), suggest that, in mouth-breathing patients, changes in the tongue musculature may contribute to several malocclusions, thus altering the shape of the craniofacial complex.…”
Section: Discussionmentioning
confidence: 72%
“…However, the posterior oral sealing is possibly adapted to be broken easily with lower nasal resistance to the airflow. 17,26,27 For those reasons, mouth breathing was objectively differentiated with incompetent lip using a CO 2 sensor, and normal nasal breathers were selected as subjects. Full-time mouth breathing was induced by occluding the nostrils with a nose clip.…”
Section: Clinical Implicationmentioning
confidence: 99%
“…Any alteration of this physiologic system may induce deficits in the development of the stomatognathic system . Studies show, with a moderate level of evidence, a correlation between atypical swallowing in children and nasal obstruction; however, little research has been conducted into the dynamics of swallowing from the oral phase to the pharyngeal phase. A study of children with acute tonsillitis and recurrent tonsillitis showed abnormally high electric activity of the masseter and infrahyoid muscles during swallowing, indicating the importance of this investigation type …”
Section: Introductionmentioning
confidence: 99%